Effects of Microalgal Food Quantity on Several Productivity-Related Parameters of the Calanoid Copepod Bestiolina similis (Calanoida: Paracalanidae) - Camus, Thomas; Rolla, Lucrezia; Jiang, Jufeng; Zeng, Chaoshu (Frontiers in Marine Science, 2021)
The influence of microalgal feeding concentration on major parameters related to culture productivity of the calanoid copepod Bestiolina similis (Paracalanidae) was investigated in a series of laboratory experiments. B. similis was fed eight different concentrations (0, 150, 300, 600, 900, 1200, 1500 and 1800 µgC l-1) of a mixed microalgal diet consisting of Tahitian strain of Isochrysis species, Pavalova 50 and Tetraselmis chuii at 1:1:1 carbon ratio. The results indicate that female daily and cumulative egg production over lifespan, egg hatching rate, naupliar and copepodite survival and development, adult female life expectancy, population growth and fecal pellet production rate (FPPR) were all significantly affected by microalgae feeding ration. Conversely, no significant influence could be established between microalgae food concentration and egg diameter or adult sex ratio. Feeding rations as low as 150 µgC l-1 led to lower egg hatching rates, survival and development, adult female life expectancy and population growth compared with the higher microalgae rations tested. B. similis fed with 1200 µgC l-1 significantly improved female egg and fecal pellet production when compared to the lower treatments and was responsible for the highest female lifespan egg production and population growth observed among all treatments. Feeding rations as high as 1500 µgC l-1 and 1800 µgC l-1 did not lead to significant improvement in any of the parameters measured. This is likely due to a saturation effect at high food concentration which is known to decrease calanoid feeding efficiency. Finally, Bestiolina similis FPPR was found to saturated at a microalgae concentration of 783.4 C l-1, indicating that CVI female ingestion did not increase significantly above this concentration. Based on the above results it is recommended that B. similis cultures should be fed at a concentration of 1200 µg l-1, and not above, as rations >1200 µg l-1 will not significantly improve any of the productivity-related parameters observed in this study. Feeding rations should never be below 783.40 C l-1 as this is the threshold level below which adult female ingestion rates become limiting.